FACTORS AFFECTING THE USE OF FORENSIC ACCOUNTING SERVICES AN EMPIRICAL STUDY ON INDONESIAN BANKS - Seto Satriyo Bayu Aji; Dekar Urumsah (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
The increase in fraud action against financial reports make many people uneasy and considering to use Forensic Accounting Services to prevent and detect fraud. This study aimed to analyse the factors affecting The Intention to Use Forensic Accounting Services in the Banking Industry in Yogyakarta. This research used the survey method and used primary data, which obtained from the population of heads of division and internal auditor staff. This research used SmartPls 2.0 to processed the data with 110 data has been processed.Results of the study find that The Perceived Benefits of Using Forensic Accounting Services affects the Attitudes towards Forensic Accounting Services. Additionally Attitudes toward Forensic Accounting Services, Government Pressure and Internal Control Systems affect the Intention to Use Forensic Accounting Services. Researchers also found that there is no affect of Perceived Risks of Forensic Accounting Services on The Attitudes towards Forensic Accounting Services, as well as Stakeholder Pressure and Time budget Pressure does not affect The Intention to Use Forensic Accounting Services.